Estudo preliminar de uma metodologia baseada no conceito de graus-dia, para previsão das fases fenológicas de culturas agrícolas - Das Virgens Filho, Jorim Sousa [UNESP]; De Lima Leite, Maysa [UNESP]; Rodrigues, João Domingos [UNESP] (My University, 1997)
This work develops a methodology (using the degree-days concept and linear regression), to forecast the duration of phenological phases in crops. An experiment was conducted in the greenhouse with three cultivars of cowpea (Vigna unguiculata (L.) Walp.), cv. Califórnia-781, Tvx 5058-09C and IT 81D-1032. The methodology was based on the relative thermal efficiency rate, determined for each species or cv. The results show that the proposed methodology may be a good alternative in works involving crops, especially because it does not require the repetition of the experiments.
Keywords: Cowpea; Degree-days; Phenology; Temperature; Vigna unguiculata